Analysis of cognitive dysfunction and its risk factors in patients with hypertension. Issue 10 (11th March 2022) - Zhuo, Xiuping; Huang, Meinv; Wu, Meifang
Abstract : Abstract: To observe whether obstructive sleep apnea syndrome (OSAS) can aggravate the cognitive dysfunction of patients with hypertension (HTN), and to explore other risk factors. One hundred one hypertensive patients were selected for information collection. After the polysomnography test, they were divided into HTN-obstructive sleep apnea (OSA) and HTN groups. The Montreal cognitive assessment and the mini-mental state examination scales were used to appraise the patients' cognitive function. Logistic regressive analysis was used to determine the risk factors of cognitive dysfunction in patients with HTN. Compared with the HTN patients, HTN-OSA patients performed worse in mini-mental state examination (25.5 ± 2.9 vs 23.5 ± 3.2; P = .01) and Montreal cognitive assessment (28 ± 1.58 vs 21.2 ± 3.96; P = .003), and patients in the HTN-OSA group seemed more likely to suffer from dementia (31% vs 66%; P < .01). The apnea-hypopnea index (AHI) in the HTN group was lower than HTN-OSA group. Through multivariate logistic regression analysis, we can found that alcohol drinking, body mass index, long-term medication, diabetes, hypercholesterolemia, coronary heart disease, and OSAS were the independent risk factors of cognitive dysfunction in patients with HTN. OSAS can aggravate the cognitive dysfunction of hypertensive patients, besides, drinking, high-body mass index, long-term medication, diabetes, hypercholesterolemia, and coronary heart disease were also the risk factors of cognitive dysfunction in patients with hypertension. The cognitive dysfunction of patients with HTN can benefit from sleep apnea treatment.